Mixed convection of Al2O3-H2O nanoliquid in a square chamber with complicated fin - Shulepova, Elena V.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2020)
Intensification of energy transport in different engineering devices is the challenge for many scientists and engineers. This problem can be solved by usage of various fins within the device and effective heat-transfer agent. The present study includes a combination of these opportunities for the heat transfer enhancement. Convective energy transport within a square enclosure having a mounted adiabatic fin and internal solid block under the influence of moving upper border and alumina/water nanoliquid has been studied. Vertical borders of the cavity are isothermal, namely, the left wall is heated, while the right one is cooled. Governing equations written using the non-primitive variables have been worked out by the finite difference technique. The special computational algorithm has been employed for the determination of the stream function magnitude at internal block taking into account the doubly connected region. Influences of the Rayleigh and Reynolds numbers, location of the internal adiabatic block and nanoparticles volume fraction on liquid flow and energy transport are studied. It has been revealed that the internal block location and nanoparticles concentration can control the intensity of heat transfer.
Keywords: Adiabatic fin; Differentially heated chamber; Finite difference method; Local adiabatic block; Mixed convection; Moved upper wall; Nanofluid